2019
DOI: 10.1093/ajcn/nqz027
|View full text |Cite
|
Sign up to set email alerts
|

Defining the plasma folate concentration associated with the red blood cell folate concentration threshold for optimal neural tube defects prevention: a population-based, randomized trial of folic acid supplementation

Abstract: Background For women of reproductive age, a population-level red blood cell (RBC) folate concentration below the threshold 906 nmol/L or 400 ng/mL indicates folate insufficiency and suboptimal neural tube defect (NTD) prevention. A corresponding population plasma/serum folate concentration threshold for optimal NTD prevention has not been established. Objective The aim of this study was to examine the association between plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 39 publications
0
49
0
1
Order By: Relevance
“…In spite of the demonstrated association between consumption of fortified wheat flour and folate status, the effectiveness of the fortification program in ameliorating FD in the population is limited. This is not only reflected in the high prevalence of FD, but also in the large proportion of women (more than 95%) who were found to have folate levels below the cut-off for optimal NTD prevention recommended by the WHO ( [33,34]). Poor household coverage with fortified wheat flour, about one-third, limits the population impact of wheat flour fortification.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the demonstrated association between consumption of fortified wheat flour and folate status, the effectiveness of the fortification program in ameliorating FD in the population is limited. This is not only reflected in the high prevalence of FD, but also in the large proportion of women (more than 95%) who were found to have folate levels below the cut-off for optimal NTD prevention recommended by the WHO ( [33,34]). Poor household coverage with fortified wheat flour, about one-third, limits the population impact of wheat flour fortification.…”
Section: Discussionmentioning
confidence: 99%
“…Folate concentrations measured in the blood using serum/plasma and RBC are indicative of short‐term and long‐term markers of folate status, respectively, through an assessment of folate intake over several previous months processed into the cells (Christensen & Rozen, ). Optimal population levels of RBC folate concentrations, and correlating serum concentrations, among women of reproductive age for predicting NTD risk have been defined (Chen et al, ; Crider et al, ). A recent systematic review and Bayesian meta‐analysis reported that both serum and RBC folate levels increase after folic acid intake from a baseline to a steady‐state, at a RBC folate concentrations needing a median for 36 weeks (95% CI = 27, 52) for 375–580 mcg/day of folic acid intake, and serum folate concentrations needing 13 weeks (95% CI = 10, 16) at 100 mcg/day folic acid intake.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have proved that excessive intake of red meats, saturated/animal fats and cholesterol is positively correlated with increased risk of CRC development, and inversely, sufficient consumption of vegetables, fruit, and fibers that are rich in cruciferous, vitamins and minerals may protect against CRC risk 12 .Folate is an essential co-factor in DNA methylation and production of antioxidants. Insufficient folate intake has been shown to be related to increased risk of adenoma occurrence and recurrence [13][14][15] .However the level of folate is difficult to evaluated because it's not only affected by the ingested food but also the BMI, vitamin B-12 and so on 16 .Therefore, homocysteine was used as a new marker which is accurately and repeatable and has been confirmed may be used as a predictor of adenoma occurrence and recurrence 13,17,18 . Homocysteine has been paid more attention by researchers because it participates in one carbon unit reaction, regulates the appropriate level of S-adenosylmethionine and participates in the normal methylation level of DNA which may account for the formation of colorectal adenoma and CRC 15 .…”
Section: Discussionmentioning
confidence: 99%